A pyrrole–carbazole photoinitiator for radical and cationic visible light LED photopolymerization. (3rd January 2023) - Li, Yang; Shaukat, Usman; Schlögl, Sandra; Xue, Tanlong; Li, Jingfang; Nie, Jun; Zhu, Xiaoqun
Graphical abstract: Highlights: A novel synthesis route to obtain a bifunctional pyrrole-carbazole-based photoinitiator (ECMO) via one-step reaction is introduced. ECMO sensitizes triarysulfonium salts and extends the absorption window of the onium salts into the visible light region. Excellent absorption of ECMO at 405 nm with hydrogen donation, colorless polymerization and radical initiation capabilities. Superior curing performance of ECMO in cationic polymerization in comparison to conventional photoinitiators is exhibited. Abstract: Driven by the growing demand towards low cost and environmentally friendly curing processes, the synthesis of visible light absorbing photoinitiators has been a significant research direction in the field of photopolymerization in the past couple of years. Herein, a novel synthesis route is introduced to obtain a bifunctional pyrrole-carbazole-based photoinitiator (ECMO) via one-step reaction. On account of its excellent absorption at 405 nm and the ability for hydrogen donation, ECMO can initiate free radical polymerization upon visible light exposure and forms colorless photopolymers. Notably, ECMO is further able to act as sensitizer for triarysulfonium salts and significantly extends the absorption window of the onium salts into the visible light spectral region. ECMO sensitized triarysulfonium salts show superior curing performance in cationic polymerization (e.g. higher final monomer conversion) compared to conventional isopropylthioxanthone/triarysulfonium hexafluorophosphate systems. In addition, thermogravimetric analysis shows that ECMO possesses exceptional thermal stability, which facilitates its practical application in photopolymerization processes.